Plasmachemical Synthesis of Nanopowders of Yttria and Zirconia from Dispersed Water-Salt-Organic Mixtures; AIP Conference Proceedings; Vol. 1938 : Isotopes: Technologies, Materials and Application (ITMA-2017) - Novoselov I. Yu. Ivan Yurievich; Karengin A. G. Aleksandr Grigorievich; Shamanin I. V. Igor Vladimirovich; Alyukov E. Evgeny; Gusev A. Alexander (2018, 2018)
Title screen